Tourism Research in Nepal: A Review of Scientific Publications Published in NepJOL - Kharel, Suman; Pasa, Rajan Binayek (KMC Research Journal, 2024)
Literature review assists as a resilient catalyst for tourism research in the academic setting as tourism studies still needs a more robust conceptual underpinning. This paper presents the results of a review of the literature on tourism from 2013 to 2024. We applied review method to maintain academic rigor. By using inclusion and exclusion criteria, the literature search included 122 research articles published in 20 different journals listed in Nepal online journal (NepJOL). The literatures were reviewed and classified into 39 micro-lines variables/themes. The content of the strategy micro-lines variables/themes was analyzed in greater depth for synthesizing findings from existing studies. This paper distinguishes three categories of approaches to the review process. First of these includes overview of the journal publishers which is followed by themes of the publications and methodology used in the studies.The study found that tourism research in Nepal has been publishing by interdisciplinary and multidisciplinary journals. The distribution of the publications themes like effect of COVID-19 Pandemic, pilgrimage tourism, cultural tourism and ecotourism having a significant share of the total publications. A significant number of studies used qualitative method, focused on urban areas and considered broader provincial or national contexts. The data sources predominantly combine primary and secondary data, reflecting a balanced approach to gathering information. However, most of the study used descriptive analysis method without ensuring reliability and validity. There is a noticeable lack of attention to advanced multivariate statistical tools and economic modeling such as growth modeling, fiscal policy modeling and tourist flow modeling.This review paper thus provides fundamentals confirming the pertinence of the review for research on tourism in Nepalese context. It also helped academics to explore the contemporary research issues and methodological gaps. We hope that the findings of the study will be acknowledged in this line and essence and also help to upgrade quality of tourism research and journal publishers.